SAT0406 Lupus Arthropathy: the Different forms of Deforming Arthropathy. (9th June 2015) - Messuti, L.; Zoli, A.; Marino, G.; Petricca, L.; Nowik, M.; Gigante, M.R.; Varriano, V.; Gremese, E.; Tolusso, B.; Ferraccioli, G.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which can affected all organs of the body. Joints are affected in up to 90% of SLE patients with a variable involvement degree from minor arthralgia without erosions or deformity to an erosive arthropathy and severe functional disability (1). Objectives: To evaluate demographic, clinical and serological characteristics of SLE patients with persistent lupus arthropathy and then to compare them with the group of patients with SLE and rheumatoid arthritis overlap disease (RHUPUS). Methods: We evaluated 574 consecutive patients with a diagnosis of SLE according to the ACR (American College of Rheumatology) criteria, of which 76% with joint involvement. We considered only the 268 patients who had active joint symptoms (arthralgia or arthritis) or who had a recent history of frequent relapse/relapse remitting arthropathy. Then we analyzed organ involvements and autoantibody profile, expecially anti-citrullinated peptides antibodies (ACPA) and Rheumatoid factor (RF). At last we evaluated the differences with RHUPUS patients. Results: Of the 268 SLE patients with persistent joint involvement (age 43.4±14.3 years, female 91.0%, disease duration 11.2±4.2 years), 71% presented the joint involvement at the onset of the lupus disease, occurring in 58% of cases with arthritis and in 42% with arthralgias, while 29% of patients developed the joint involvement in the follow-up; among them, 63% presented arthralgia and only 37% arthritis. 17 patients had RHUPUS. When we compared the 17 patients with RHUPUS and 251 patients with lupus arthropathy, patients with RHUPUS are tendentially older than patients with SLE arthropathy (49.6±13.3 vs 43.0±14.3 years, respectively, p=0.06) even though they had a shorter disease duration (6.8±5.1 vs 11.5±8.4 years, respectively, p=0.02). They also had more serositic involvement but a minor skin and renal involvement. In addition, the patients with RHUPUS had a more positivity percentage of anti-SSA, ACPA (47.1% vs 1.2%, p≤0.001) and RF (64.7% vs 16.3%), a more erosive arthropathy and they needed aggressive therapy. Moreover, in the lupus arthropathy, the RF positivity is similar between SLE patients with arthritic involvement and patients with only arthralgias (16.3% vs 16.4%, respectively, p=0.97). Conclusions: This study seems to show that there are not demographic, clinical or laboratory characteristics that can early distinguish patients with arthralgia and arthritis. Moreover RHUPUS seems confirmed as an overlap syndrome characterized by the presence of bone erosions and the positivity of ACPA in association with arthritis. References: Fernantez A et al. Lupus arthropathy: a case series of patients with rhupus. Clinical Rheumatology 2006; 25: 164–7. Disclosure of Interest: None declared